Content Considerations in High School Musical Theater Show Selection - (:unkn) unknown (My University, 2024)
Many high schools present musical theater productions annually. In some cases, high school students present material that could be considered controversial or uncomfortable for performers, their directors, or audiences. The purpose of this study was to examine content issues of musicals that high school theater directors must consider when selecting a show for high school performance. Topics analyzed included: sexualization of characters and sexism, references to sexual activities including kissing and simulation of sexual acts; profanity, racially-defined Black, Indigenous, People of Color (BIPOC) roles, racism, LGBTQ characters, gun violence, the use of alcohol and drugs, domestic violence, direct religious messaging or plots with religious connections, potentially controversial political elements, and elements of physical and mental health. This research used a mixed-methods approach where a survey, of mostly quantitative questions with some opportunities for qualitative responses, was given to 27 high school musical theater directors. Interviews were also conducted with three musical theater directors in various sized communities, with varying years of experience. Survey data revealed that audiences rarely reacted negatively to a show that was presented with mature content. Data analysis produced the following emergent themes, (1) Director comfort in working with the material and with students; (2) Interactions with administration; (3) Student comfort and safety; (4) Educating students about potentially controversial topics; and (5) Being aware of community comfort, morals, and values. This study provided some insights into the thoughts and comfort-levels of directors, their students, and their communities regarding a range of potentially controversial content considerations. Directors’ perspectives provided models for handling many of the topics listed. This research may help directors determine what is too mature for them, their students, or their community. This will hopefully lead to more students, directors, and audiences enjoying high school musical theater both on stage, behind the scenes, and in the audience.
Keywords: music education; musical theater; script content; show selection; student comfort; theater education